EVALUATING THE IMPACT OF NURSE-LED INTERVENTIONS ON PATIENT OUTCOMES, SATISFACTION, AND HEALTHCARE QUALITY: A COMPREHENSIVE STUDY IN SAUDI ARABIAN HOSPITALS - Ebtihal Abdullah Marzooq Al Nasseb, Badour Dahham Kareem Alshammari, Amal Daham Kareem Alshammari, Tahani Shulaywih Owayyish Alzabeni, Saad Alew Aldafere, Fatmah Bady Fraujan Aldafeery, Shuaa Qassim Ashui Alanazi; Amwag Marwah Marji Al-Dhafiri, Reem hendi alharbi (Chelonian Research Foundation, 2022)
Nurse-led interventions have gained considerable attention in recent years due to their potential to improve patient outcomes, satisfaction, and overall healthcare quality. This comprehensive study aims to evaluate the impact of various nurse-led interventions on these factors in Saudi Arabian hospitals. The research employs a mixed-methods approach, combining quantitative data analysis with qualitative insights from nurses, patients, and other healthcare professionals. The study focuses on seven key areas: patient education, early mobility protocols, pain management, multidisciplinary rounds, pressure ulcer prevention, evidence-based practice implementation, and discharge planning. By conducting this research across multiple hospitals in Saudi Arabia, the authors seek to provide valuable insights into the critical role nurses play in enhancing patient care and healthcare quality.